Handbook of discrete-valued time series - Davis, Richard A.; Holan, Scott H.; Lund, Robert; Ravishanker, Nalini (Chapman & Hall/CRC handbooks of modern statistical methods, 2016)
Handbook of Discrete-Valued Time Series presents state-of-the-art methods for modeling time series of counts and incorporates frequentist and Bayesian approaches for discrete-valued spatio-temporal data and multivariate data. While the book focuses on time series of counts, some of the techniques discussed can be applied to other types of discrete-valued time series, such as binary-valued or categorical time series.